PSYCHOPHYSIOLOGICAL MANIFESTATIONS OF THE INFLUENCE OF STRESS ON HUMAN HEALTH - Sirenko , Olena (Collection of scientific papers «ΛΌГOΣ», 2023)
Stress weakens our immunity, making us vulnerable to various infections. Many pathologies, the main cause of which is the experience of stress, include heart attack, depression, anxiety, stroke, weakening of the immune system and as a result, vulnerability to all kinds of infections, from the common cold and herpes to complex ones like AIDS, some forms of cancer, rheumatoid arthritis or multiple sclerosis. The critical value of stress, after which it becomes destructive, is different for each person. It is very important not to miss the characteristic signs that signal that we are approaching such a peak. Stresses can be acute and chronic, accumulating gradually. It is well known that even a single acute stress, caused by, for example, a hopeless situation, can cause serious illness and even death.